Greg News: estratégias humorísticas utilizadas na eleição presidencial brasileira de 2018 - Souza, Sônia Maria Reis de (2024)
This research carries out an audiovisual and discursive analysis of Greg News (2017-2024) focusing on the program's political positioning in the context that precedes the 2018 presidential election in Brazil, marked by the rise of the extreme right. Relying on an editorial line that announces itself as leftist and, therefore, contrary to the reactionaryism revealed in the country, especially over the last decade, the program produced by HBO Brazil and presented by Gregorio Duvivier has a hybrid format between opinion journalism and humor: information and the judgment about current facts in the political universe are combined with the use of humor as a critical resource. Starting from the hypothesis that Greg News cannot be considered an effective left-wing political satire, since, as part of the liberal media, the program does not confront certain instances of neoliberalism, the general objective of this dissertation is to carry out an audiovisual analysis of the program in seeks to demarcate its position in relation to the context that precedes the 2018 Brazilian presidential elections, taking into account the position of the pre-candidates, as well as the respective economic and social policies aligned with them. The specific objectives are: (1) define the lineages and genera into which the program fits; (2) identify your humor strategies; (3) analyze the impacts of the program on the political scenario and the impacts of the political context on the program. Four representative episodes of the program were selected for analysis, which are located in the context that precedes this electoral process. The methodology adopted to analyze the episodes is based on audiovisual analysis, based mainly on Jacques Aumont et al. (2001), and in the categories of discourse analysis applied to audiovisual, taking Foucault (2008) and Orlandi (2009) as the main theoretical apparatus. In addition to the historical reconstruction of humor in Brazilian audiovisual, canonical references on humor were also mobilized, in theoretical terms, such as Bergson (2014), Minois (2003), Freud (2017) and Raskin (1985), among others, and on democracy and politics, in particular Bobbio (2006, 2000) and Foucault (2012, 2010, 1999). Articulating core audiovisual issues – humor, entertainment, journalism, politics, public sphere, engagement and digital activism –, the dissertation is structured into three chapters that deal sequentially with the following subjects: the professional trajectory and political engagement of Gregorio Duvivier, the aspects that characterize the program and its backstage; the humor strategies used in Greg News; analysis of selected episodes.